OCCURRENCE OF SALMONELLA SPP. IN BROILER CHICKEN FECES IN THE CENTRAL REGION OF THE STATE OF MINAS GERAIS, BRAZIL - Júnior Lúcio, Caio; Bittencourt Mathias, Joana; Marcos Lauer Júnior, Claudio; Jaqueline Viana Soares Flores, Silvia; Martinez Xavier Alves Teixeira, Fernanda (Revista de Patologia Tropical / Journal of Tropical Pathology, 2019)
Bacteria of the genus Salmonella are gram-negative rods, facultative anaerobic non-spore formers, which may or may not be flagellated. These bacteria are frequently detected in poultry products and are important in animal and public health. The purpose of this study was to investigate the occurrence of Salmonella spp. in feces from broiler chicken litters located in municipalities of the central region of the state of Minas Gerais, Brazil. The study analyzed 845 feces samples from different poultry farms collected between September 2016 and March 2017. Pre-enrichment broths, specific selective broths and selective indicator agar were used for the analyses. The suspected isolates were submitted to biochemical testing and serotyping with “O” and “H” antisera to identify the Salmonella serotypes. The results showed that 213 feces samples were contaminated with Salmonella, and the serotypes found were: S. Minnesota, S. Sandiego, S. Schwarzengrund, S. Infantis, S. Hadar, S. enterica subsp. enterica (O: 4.5), S. Montevideo, S. Miami, S. Heidelberg, S. Cerro, S. Ndolo, S. Panama, S. Anatum, S. Tennessee, S. Agona, S. Newport and S. Muenster. The Minnesota serotype was predominant among the isolates investigated. Actions to improve the biosafety of commercial poultry farms are necessary to prevent possible contamination of poultry products that endanger human health.